Reducing biomass utilization in the ethiopia energy system: A national modeling analysis - Yurnaidi, Zulfikar; Kim, Suduk (Energies, 2018)
With its target of becoming a middle-income country by 2025, Ethiopia has set ambitious targets in its Growth Transformation Plan (GTP) II, such as increasing power generation capacity from 4.18 to 17.21 GW during the 2016-2020 period. However, according to the 2015 IEA energy balance table, Ethiopia depends heavily on biomass for its final energy use. In final energy service sectors, biomass takes more than 90% of the final energy consumption (36.9 out of 40.9 MTOE), 99% of which is consumed in the residential sector. Therefore, it is very important to achieve biomass utilization in the energy sector targets of Ethiopia. This paper aims to analyze the biomass consumption in the Ethiopia energy system, and discuss related policies. An integrated assessment model is chosen for its national energy modeling, and to simulate policy scenarios in a comprehensive and consistent manner. After building a reference case, three scenarios are developed: (1) higher Gross Domestic Product (GDP) and urbanization rate, (2) efficiency improvement of biomass technologies, and (3) sensitivity analysis of urbanization. It is found that biomass still holds the largest share of energy consumption in the future, which increases even more in the high GDP and urbanization scenario. Increasing efficiency of biomass technology can reduce biomass consumption, but the "rebound effect" is observed, which increases the energy service demand, thus dampening the effect of biomass efficiency improvement.
Keywords: Energy model; Ethiopia; Gross domestic products; Integrated assessment models; Middle-income countries; Power generation capacities; Urban-rural; Urbanization; Biomass; Efficiency; Ethiopia; National energy modeling; Urban rural; Urbanization